O’ZBEKISTON RESPUBLIKASIDA JINOYATCHILIK TURLARI VA UNING HUDUDIY TAFOVUTLARI (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article describes the crimes committed on the territory of the Republic of Uzbekistan, their socio-geographical aspects, territorial recommendations of types of crime, gives relevant conclusions and recommendations on the topic.